1971
DOI: 10.1203/00006450-197109000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid on Fatty Acid Biosynthesis in Brain

Abstract: ExtractTriodothyronine (T 3 ) was given daily by injection to rats from 1 day of age to 2 hr prior to death. In the brain microsomal fraction of 5-to 6-day-old animals, incorporation of malonyl-CoA into total fatty acids increased from 0.9 to 2.25 m/imoles/mg protein. Although thyroid increased precursor incorporation into total fatty acids in other age groups, the difference was not statistically significant. Increased precursor incorporation was entirely due to increased formation of saturated fatty acids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Inasmuch as the ovine fetal thyroid begins t o function at about 50 days gestation ( 5 ) and the fetuses were presumably euthyroid between 5 0 and 90-110 days, the extent of thyroxine dependence of early ovine fetal brain development is not clear. However, the present data are in general agreement with an earlier report of Grippo and Menkes (21) which showed that fatty acid elongation was reduced in rats made hypothyroid at birth. These authors suggested that iodothyronines may stimulate the brain microsomal-fatty acid elongation system involved in the synthesis of saturated fatty acids characteristic for myelin lipids.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Inasmuch as the ovine fetal thyroid begins t o function at about 50 days gestation ( 5 ) and the fetuses were presumably euthyroid between 5 0 and 90-110 days, the extent of thyroxine dependence of early ovine fetal brain development is not clear. However, the present data are in general agreement with an earlier report of Grippo and Menkes (21) which showed that fatty acid elongation was reduced in rats made hypothyroid at birth. These authors suggested that iodothyronines may stimulate the brain microsomal-fatty acid elongation system involved in the synthesis of saturated fatty acids characteristic for myelin lipids.…”
Section: Discussionsupporting
confidence: 83%
“…Its chemical properties (for review see Reference 8) and variations of the plasma levels of the factor in different pathologic conditions have been the subject of several studies (e.g., 11,13,18,19,22). For newborn infants, some authors reported low values (1, 3, 7, 23), whereas others have found normal adult levels (6,14,17,21,24). However, all of these investigations were carried out with bioassays, such as differential clot solubilities, which from the quantitative point of view are of questionable reliability.…”
Section: Extractmentioning
confidence: 99%
“…On the other hand, the effect of thyroxine (T4) in the developing brain metabolism is well established [24][25][26]. T4 augments brain cholesterol [24] and fatty acid synthesis [25] while T4 defi ciency retards dendritic arborization and myelination [26].…”
Section: Introductionmentioning
confidence: 99%